Estrategias metodológicas y su influencia en la lectoescritura en los estudiantes de la Escuela Federico González Suárez, Montalvo. 2022 - Trujillo Moreno, Dayana Mishell (2023)
This research was carried out with the objective of overcoming the problems that exist in the educational environment, one of them is the learning problems that students present in terms of reading and writing, in this way, allowing them to feel motivated and safe as they progress through the educational process. Education must develop the process of reading and writing to produce a new generation of critical, determined and reflective students who are able to function and develop meaningful learning to perform better in social and cultural domains. The lack of teaching materials and innovative strategies on the part of teachers is one of the factors that contribute to the lack of interest of students in the classroom. To achieve satisfactory learning results, teachers must receive adequate training, so it is the job of professionals to continuously learn to improve teaching. Reading and writing are the foundations of quality teaching, and teachers must develop skills and methods to guide them in this vitally important process. Reading is one of the best allies in student development, so different approaches must be applied so that students learn differently. It was concluded that the use of innovative teaching strategies had a positive impact on literacy learning and improved the academic performance of students; Both the students and their teachers felt motivated in their daily tasks and had a greater participation in the teaching process.